До питання відшкодування (компенсації) шкоди потерпілому у кримінальному процесі України - Глобенко, Г. І.; Globenko, G. I.; ORCID: http://orcid.org/0000-0002-1533-9213 (Право і безпека. – 2017. – № 2 (65). – С. 71–75, 2017)
Проаналізовано положення кримінального процесуального законодавства України, що стосуються інституту відшкодування (компенсації) шкоди. Висвітлено думки науковців з питань, що досліджуються, та надано їх оцінку. Наголошено на тому, що для сторони обвинувачення право на відшкодування (компенсацію) шкоди є одним з основних засобів забезпечення її прав, свобод та законних інтересів у кримінальному провадженні. Обґрунтовано пропозиції з удосконалення процесуальних норм, що стосуються предмета дослідження.

The procedural institute of reimbursement (compensation) of the caused harm to a victim by a criminal offense is a complex legal phenomenon, in the structure of which it is expedient to allocate organizational and procedural aspects. Reimbursement (compensation) in criminal proceedings may be provided through voluntary redress, filing a civil claim, a pledge to execute a sentence in respect of property fines; compensation of damage at the expense of the State Budget of Ukraine, criminal and legal restitution, etc. The most favorable and optimal for the victim and the civil plaintiff form of reimbursement (compensation) of the caused harm is the criminal and legal restitution. The state provides an opportunity for a person, who has suffered property and / or moral damage by a criminal offense to restore the position by means of filing a civil claim, the form and content of which must comply with the requirements established by civil legal proceedings. The mentioned procedure is complicated and, as a rule, requires the application of an ordinary citizen to the appropriate specialist. This state of affairs indicates that a person who has suffered as a result of the wrongful acts committed against this person should bear the appropriate material expenses for the assertion of own property and / or moral rights. The outlined innovation of the legislator in the current economic situation of a large number of citizens of the state is extremely inappropriate.

Проанализированы положения уголовного процессуального законодательства Украины, касающиеся института возмещения (компенсации) вреда. Освещены точки зрения учёных по исследуемым вопросам и предоставлена их оценка. Акцентировано внимание на том, что для стороны обвинения право на возмещение (компенсацию) ущерба является одним из основных средств обеспечения прав, свобод и законных интересов в уголовном производстве. Обоснованы предложения по совершенствованию процессуальных норм, касающихся предмета исследования.
К вопросу возмещения (компенсации) вреда потерпевшему в уголовном процессе Украины
On the issue of reimbursement (compensation of the caused harm to the victim in the criminal procedure of Ukraine
Глобенко, Г. І. До питання відшкодування (компенсації) шкоди потерпілому у кримінальному процесі України / Г. І. Глобенко // Право і безпека. – 2017. – № 2 (65). – С. 71–75.
Глобенко Г. І. "До питання відшкодування (компенсації) шкоди потерпілому у кримінальному процесі України." Право і Безпека 2 (2017): 71-75.
Globenko, G.I. (2017), “On the issue of reimbursement (compensation) of the caused harm to the victim in the criminal procedure of Ukraine” [“Do pytannia vidshkoduvannia (kompensatsii) shkody poterpilomu u kryminalnomu protsesi Ukrainy”], Pravo i Bezpeka, No. 2, pp. 71–75.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне правопорушення; потерпілий; заподіяна шкода; відшкодування; компенсація; цивільний позов; уголовное правонарушение; потерпевший; причинённый ущерб; возмещение; компенсация; гражданский иск; criminal procedure; criminal offense; institute; victim; caused harm; reimbursement; compensation; civil claim